Month 60 Outcomes After Treatment Initiation With Anti–Vascular Endothelial Growth Factor Therapy for Macular Edema Due to Central Retinal or Hemiretinal Vein Occlusion - Scott, Ingrid U.; VanVeldhuisen, Paul C.; Oden, Neal L.; Ip, Michael S.; Blodi, Barbara A. (American journal of ophthalmology, 2022)
To investigate 5-year outcomes in eyes initially treated with aflibercept or bevacizumab for macular edema due to central retinal or hemiretinal vein occlusion. Long-term follow-up (LTF) after a randomized clinical trial from 64 centers in the United States. Participants were followed up to 60 months and treated at investigator discretion after completing the 12-month treatment protocol. Main outcomes were visual acuity letter score (VALS) and central subfield thickness (CST) on optical coherence tomography. Seventy-five percent (248/330) of eligible participants completed at least 1 visit between months 24 and 60, and 45% completed the month 60 visit. Among participants completing month 60, overall mean VALS improvement over baseline was 13.5 (95% CI: 9.6, 17.5), less than the mean improvement of 20.6 (95% CI: 18.7, 22.4) observed at month 12, with no significant differences between originally assigned study groups. Further, 66% (99/150) had at least 1 treatment between months 48 and 60 with a mean (SD) of 3.41 (3.69) treatments over this period. Mean CST was 671 μm at baseline and 261 μm (95% CI: 241.2, 280.9) at month 60. Although VALS improved substantially when patients were treated per protocol through month 12, improvement lessened when treatment was at investigator discretion and fewer treatments were received although VALS remained markedly improved over baseline through year 5. Most patients continued to receive treatment in year 5. This suggests that continued monitoring and, if warranted, treatment with anti-VEGF therapy benefits patients with macular edema associated with central retinal or hemiretinal vein occlusion. Publication of this article is sponsored by the American Ophthalmological Society.